A blessed shore : England and Bohemia from Chaucer to Shakespeare - Thomas, Alfred (2007)
Imitatio Mariae : Anne of Bohemia as cultural and religious mediatrix – Imperial designs : art and ideology at the Ricardian and Luxembourg courts – "Master adversary" : Wyclif's influence in Bohemia – "The Wycliffite woman" : reading women in fifteenth-century Bohemia – Peregrinus et alter Ulysses : Leo of Rožmitál's mission to England (1466) – Shakespeare's Bohemia : English men and women in Renaissance Prague – Three men in a boat : Waldstein, Hollar, and Comenius in seventeenth-century England